Dynamics of Worklife Balance, Workload, Job Stress and Employee Performance - Retnowati, Putu Ayu; Darma, Gede Sri (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
The aim of this study is to analyze the direct influence of work-life balance and workload on work-related stress and employee performance. Furthermore, it seeks to examine the direct impact of job-related stress on employee productivity, as well as the indirect impact of work-life balance and burden on employee productivity through job-related stress. The research was conducted on female employees who have numerous occupations at the Regional Secretariat of Badung Regency. The research population consisted of 275 female employees who hold dual roles within the organization. A sample of 153 participants was selected using the Slovin formula, ensuring a representative distribution for the study. Data were collected through a validated questionnaire utilizing a semantic differential scale ranging from 1 to 10. The research employed a quantitative approach, utilizing using Structural Equation Modeling (SEM) for data analysis. The stages of testing the research data included: Assessing the validity and reliability of the measurement instruments, Conducting a confirmatory factor analysis (CFA) to evaluate the measurement model, Performing goodness-of-fit tests to ensure the model's adequacy, and analyzing the structural model to test the hypothesized relationships among the variables. The analytical results demonstrate that work-life balance has a direct and negative effect on workplace stress, while it has a significant and positive effect on employee performance. The level of work assigned has a direct and significant effect on the stress experienced in the job, ultimately leading to a negative impact on performance. Simultaneously, work-related stress has a harmful and significant effect on employees' performance. Work stress does not significantly act as a mediator between work-life balance, workload, and employee performance.